Post-pandemic barriers to inferential and critical reading: a mixed-methods study - Albarico, Josh Erick G.; Deiparine, Marcelina S. (Institute of Advanced Engineering and Science, 2025)
The Program for International Student Assessment (PISA) 2018 and 2022 results expose the alarming problem in the Philippines’ reading comprehension, a situation worsened by pandemic-related disruptions. This study investigates the specific reading comprehension skills where students struggle most and the factors contributing to these difficulties in a post-pandemic context. Using an explanatory sequential design, the researchers conducted reading assessments for the 30 grade 7 students, followed by interviews with 12 students and 5 teachers selected through purposive sampling. Descriptive statistics indicated that students faced the most challenges with inferential and critical-level skills, highlighting gaps in higher-order thinking. Thematic analysis identified contributing factors, including lack of reading engagement, lack of linguistic competence, remote learning repercussions, challenges from screen dependency, and environmental influences. These challenges highlight the long-term impact of the pandemic on reading development. To address this, the educational system must strengthen teacher training in reading instruction to promote active student engagement. Educators are encouraged to develop age- and interest-appropriate reading materials, use technology in reading instruction, and foster collaboration between schools, communities, and families. Targeted interventions are essential to rebuild and enhance students’ reading comprehension skills, ensuring they can meet the demands of higher-order thinking in a post-pandemic world.